A New Validation Approach of a New Three-Phase High Voltage Power Supply for Microwaves Generators with one Magnetron by Phase - M. Bassoui; M. Ferfra; M. Chraygane (Institute of Advanced Engineering and Science, 2016)
In order to validating the new three-phase High voltage power supply for microwave generators with one magnetron by phase, this paper presents a new validation approach to evaluate the proposed model with several evaluations. This approach is based on the calculation and measurement of the performance and the power factor of this new three-phase power supply, also the study of the operation of this new system in case of failure. The design of this power supply is composed of new three-phase transformer with magnetic shunt, supplying by phase a voltage doubler cell composed of a capacitor and a diode. Each cell in turn, supplies a single magnetron. In this paper we have presented the new three-phase transformer by its equivalent model; it’s a π quadruple model composed of storable inductances able to translating the nonlinear saturation phenomena for stabilization of the magnetron current. The voltage and current curves obtained by simulation with MATLAB SIMULINK are in good conformity with those obtained by experimental of conventional power supply using a single phase transformer for one magnetron. The same curves will allow us to plot the instantaneous power absorbed by each magnetron. This leads to determine the average power emitted by each magnetron, and establish the balance of the power microwave generator by computing its performance which is compared to that obtained from experimental. After that we will compute the power factor of this power supply and we will study its operation in case of failure of one or two magnetrons.